East 43rd Street - Battersby, Alan (Cambridge English readers. Level 5, 2000)
New York on a cold, wet evening, six days before Christmas. Nathan Marley, an old-fashioned private investigator in a modern world, is relaxing in McFadden's Bar. An expensively-dressed woman walks in the bar, buys a drink with a hundred-dollar bill, and leaves without her change. Marley decides to follow her, and suddenly Christmas becomes a lot more exciting than he expected.